The Siesta Habit is Associated with a Decreased Risk of Rupture of Intracranial Aneurysms - Kang, Huibin; Feng, Xin; Zhang, Baorui; Guo, Erkang; Wang, Luyao; Qian, Zenghui; Liu, Peng; Wen, Xiaolong; Xu, Wenjuan; Li, Youxiang; Jiang, Chuhan; Wu, Zhongxue; et al. (Frontiers in Neurology, 2017)
Background Previous studies have examined an association between the siesta habit and hypertension, as well as coronary heart disease. However, the relationship between a siesta and the risk of rupture of an intracranial aneurysm (IA) has not yet been established. We aimed to investigate the effects of a siesta on the risk of rupture of IAs. Methods We prospectively enrolled consecutive patients diagnosed with IAs at our hospital between January 2016 and December 2016. Univariate and multivariate logistic regression analysis were performed to identify independent risk factors associated with IA rupture. Results We studied 581 consecutive patients with 514 unruptured and 120 ruptured aneurysms. Univariate analysis demonstrated that hypertension, hyperlipidemia, diabetes mellitus, cigarette smoking, location, size, as well as shape and aspect ratio were associated with the risk of rupture of IAs. Multivariate analysis identified hypertension [odds ratio (OR) 1.68, 95% confidence interval (CI) 1.03–2.73], hyperlipidemia (OR 0.25, 95% CI 0.08–0.72), current cigarette smoking ≥20 cigarettes/day (d) (OR 3.48, 95% CI 1.63–7.47), siesta (siesta time <1 h, OR 0.49, 95% CI 0.24–0.98 and siesta time ≥1 h, OR 0.32, 95% CI 0.19–0.57), location of largest aneurysm on the anterior communicating and internal carotid-posterior communicating artery (PCOM) (anterior communicating artery OR 16.27, 95% CI 7.40–35.79 and PCOM OR 11.21, 95% CI 5.15–24.43), and size of aneurysm ≥7 mm (OR 2.19, 95% CI 1.21–3.97) as independent strong risk factors associated with risk of aneurysm rupture. Conclusion In the present study, we found that a habitual siesta is a new predictive factor to assess the risk of rupture of an IA. We found the siesta habit may reduce the risk of aneurysm rupture. We also found that hypertension, hyperlipidemia, cigarette smoking, location, and size of aneurysm were associated with the risk of rupture of IAs.